Recurrent spontaneous subcutaneous emphysema in a patient with rheumatoid arthritis - Adelowo, Olufemi (BMJ Case Rep, 2015)
Pulmonary air leak syndromes are extremely rare complications of systemic autoimmune connective tissue diseases and the occurrence of spontaneous subcutaneous emphysema (SSE) from pulmonary leak in the absence of pneumothorax or pneumomediastinum is even rarer. We report a case of recurrent SSE in a patient with rheumatoid arthritis and interstitial lung disease. The SSE was managed conservatively each time and it resorbed over several days. There has been no previous documented report of SSE in the absence of pneumomediastinum, pneumothorax or pulmonary nodules in a patient with RA.